Navigating Higher Education: Factors Contributing to Former Foster Care Youth’s Graduation from Post-Secondary Education - Elliott, Sean; Fitzgerald, Carolyn (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2022)
This study identifies factors contributing to the success of foster care alumni (FCA) who graduate from post-secondary education (PSE), despite institutions devoting little effort to making PSE accessible to FCA. Nine FCA PSE graduates were interviewed about their success. Responses were analyzed using an exploratory method to identify themes related to factors deemed critical to theirgraduation from PSE. Ferguson’s (2019) conceptual model of a Student Development Pathway was used to organize findings; success factors were analyzed accordingly to their role in the Preparation, Awareness, Engagement, Transition, and Persistence phases. Findings suggest the role of coaching and caring adults was most notable in the Preparation, Engagement, and Transitional phases to PSE. Determination factored predominantly during the Persistence phase, and Resistance was most associated with the Preparation and Persistence phases. Findings also indicated numerous untapped opportunities and initiatives that could make PSE more accessible and achievable for FCA.